Genotoxic, mutagenic and cytotoxic effects of the commercial dye CI Disperse Blue 291 in the human hepatic cell line HepG2 - Tsuboy, M. S.; Angeli, J. P. F. [UNESP]; Mantovani, M. S. [UNESP]; Knasmueller, S.; Umbuzeiro, G. A.; Ribeiro, L. R. [UNESP] (Elsevier B.V., 2007)
Textile dyes are discarded into the aquatic ecosystem via industrial effluents and potentially expose humans and local biota to adverse effects. The commercial dye CI Disperse Blue 291 which contains the aminoazobenzene 2-[(2-bromo-4,6-dinitrophenyl)azo]-5(diethylamino)-4-methoxyacetanilide (CAS registry no. 56548-64-2), was tested for genotoxicity and cytotoxicity in the human hepatoma cell line HepG2, using the comet assay, micronucleus (MN) test and a cell viability test. Five different concentrations of the test compound were examined: 200 mu g/ml, 400 mu g/ml, 600 mu g/ml, 800 mu g/ml and 1000 mu g/ml. An increase in comet tail length and in the frequency of MN was detected with exposure of cells to concentrations of the commercial dye from 400 pg/ml. Furthermore, the dye was found to decrease cell viability. The results of this study demonstrate for the first time the genotoxic and mutagenic effects of the dye CI Disperse Blue 291 in mammalian cells, thus stressing the need to develop non-mutagenic dyes and to invest in improving the treatment of effluents. These measures will help to prevent harmful effects that these compounds can have on humans and aquatic organisms that come in contact with them. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: azo dye; CI Disperse Blue 291; HepG2; comet assay; micronucleus test; cell viability